2015
DOI: 10.1371/journal.pone.0130820
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Ethnicity Are Independent Factors Associated with Lower Urinary Tract Symptoms

Abstract: ObjectivesTo determine the lower urinary tract symptoms (LUTS) profile and factors affecting its degree of severity including cardiovascular risk profile, age, ethnicity, education level and prostate volume in a multiethnic Asian setting.Materials and MethodsWe conducted a cross-sectional study of 1021 men aged 40–79 years with no clinical evidence of prostate cancer, prostate surgery or 5α-reductase inhibitor treatment of known prostate conditions. The severity of LUTS was assessed using the International Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Similar to other studies, our data showed an increase in the prevalence of moderate to severe LUTS with advancing age. The prevalence of LUTS in our study was much lower compared with other studies based in Europe [ 3 5 , 7 , 14 ], the US [ 6 ], South America [ 18 ], Hong Kong [ 12 ] and other Asian countries [ 3 , 10 ], especially among people aged over 50 years. Nevertheless, a similar prevalence was found between this study and another 2 population-based studies in Norway [ 8 ] and Singapore [ 9 ], for men who were younger than 50 and 70 years, respectively.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Similar to other studies, our data showed an increase in the prevalence of moderate to severe LUTS with advancing age. The prevalence of LUTS in our study was much lower compared with other studies based in Europe [ 3 5 , 7 , 14 ], the US [ 6 ], South America [ 18 ], Hong Kong [ 12 ] and other Asian countries [ 3 , 10 ], especially among people aged over 50 years. Nevertheless, a similar prevalence was found between this study and another 2 population-based studies in Norway [ 8 ] and Singapore [ 9 ], for men who were younger than 50 and 70 years, respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…Nevertheless, a similar prevalence was found between this study and another 2 population-based studies in Norway [ 8 ] and Singapore [ 9 ], for men who were younger than 50 and 70 years, respectively. This difference in the prevalence may be partially due to the different study designs (face-to-face interviews or self-completed questionnaires), population characteristics such as their jobs or areas, and people's ethnicity and life habits [ 3 , 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as mentioned in the Introduction section, various types of diseases and chronic illness are known to cause increased urinary frequency. Interestingly, these pollakiuria‐related pathological conditions are thought to have an association with excessive salt intake . Therefore, we focused on daily salt intake in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, increased urinary frequency causes various pathophysiological conditions and lifestyle diseases, such as cardiovascular disease, diabetes mellitus, renal dysfunction, lower urinary obstruction and primary sleep disorders . Most previous reports suggest that hypertension strongly influences LUTS, including pollakiuria, and one of the chief causative factors of hypertension is excessive salt intake . Furthermore, salt intake is known to be a direct and/or indirect cause of pollakiuria‐related diseases, such as hypertension, cardiovascular disease and diabetic nephropathy .…”
Section: Introductionmentioning
confidence: 99%